2008
DOI: 10.1002/jor.20758
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide induced repression of icaADBC transcription and biofilm development in Staphylococcus epidermidis

Abstract: Expression of the icaADBC-encoded polysaccharide intercellular adhesion by Staphylococcus epidermidis promotes biofilm formation and represents an important virulence factor in biomaterial-related infections following orthopedic surgery. Biofilm development by the pathogen can be viewed as a protective reaction to environmental stressors including osmotic stress, thermal stress, and antimicrobial chemotherapy. Oxidative stress, arising from the release of toxic oxygen radicals by polymorphonuclear cells, is en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 27 publications
2
22
0
Order By: Relevance
“…These data are consistent with the role of icaR as a transcriptional repressor of the ica operon. 13,20 However the dramatic activation of icaR transcription in various PI concentrations was associated with a relatively modest decrease in icaADBC transcription indicating that PI can also influence ica operon expression and biofilm independently of icaR. Growth of S. epidermidis in H 2 O 2 has a smilar effect to PI 20 whereas exposure to 4% ethanol has the opposite effect leading to icaR repression and activation of icaADBC.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…These data are consistent with the role of icaR as a transcriptional repressor of the ica operon. 13,20 However the dramatic activation of icaR transcription in various PI concentrations was associated with a relatively modest decrease in icaADBC transcription indicating that PI can also influence ica operon expression and biofilm independently of icaR. Growth of S. epidermidis in H 2 O 2 has a smilar effect to PI 20 whereas exposure to 4% ethanol has the opposite effect leading to icaR repression and activation of icaADBC.…”
Section: Discussionmentioning
confidence: 98%
“…Determinations of MIC and minimum bacteriocidal concentration (MBC) were performed as previously described. 19,20 Biofilm Assays Semi-quantitative determinations of biofilm formation in 96-well tissue culture plates (Nunc, Denmark) using bacteria grown at 378C in BHI, and BHI supplemented with 0.17%, 0.35%, or 0.7% of PI were performed as described previously. [26][27][28] After overnight incubation at 378C, plates were washed three times with distilled H 2 O and dried for 1 h at 568C prior to staining adherent biofilm with a 0.4% crystal violet solution for 15 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…aureus biofilm formation is a multifactorial process that progresses through coordinated phases. Particularly important is the early growth phase, when the bacterium strongly attaches to a substrate, which is mediated by cell surface factors that may include autolysin (51), teichoic acids (52), or polysaccharide intercellular adhesin (PIA), the product of the ica gene (53), whose expression promotes colonization and biofilm formation, especially during environmental stress (54,55) and in the course of a device-related infection (56). We found that np and NO-np significantly inhibited bacterial adhesion to plastic and glass surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress inactivates AbfR, which acts as a repressor of abfR-SERP2195-gpxA operon. It has been shown that mild oxidative stress down-regulates S. epidermidis biofilm development (5,6,66). Similarly, we may speculate that oxidative stress acts as a signal to modulate S. epidermidis key virulence properties through AbfR.…”
Section: Discussionmentioning
confidence: 99%